Memperkuat Warisan Budaya Tionghoa melalui Media Sosial di Kalangan Generasi Muda - Gio, Gio; Pandrianto, Nigar (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
This study analyzes the role of the Instagram account @Chinese_Server in introducing and preserving Chinese cultural values among young Chinese-Indonesian generations. Using a qualitative approach with a case study method, the research explores how social media serves as an effective cultural communication tool in the fast-paced digital era. Data were collected through in-depth interviews with the account manager, cultural academics, social media specialists, and followers of @Chinese_Server. Additionally, observations were conducted on the account’s content to examine various types of posts, including Chinese history, traditions, culinary arts, and cultural celebrations, as well as audience interactions through interactive features. The findings reveal that Instagram, as a visually driven platform, effectively conveys cultural information through creative, engaging, and educational content. The account successfully fosters cultural awareness, engagement, and pride among younger generations of Chinese Indonesians. This study offers new insights into the use of social media for cultural preservation, emphasizing digital communication strategies and their critical role in promoting cultural identity amidst globalization and modernization trends. Penelitian ini menganalisis peran akun Instagram @Chinese_Server dalam pengenalan dan pelestarian nilai-nilai budaya Tionghoa di kalangan generasi muda keturunan Tionghoa di Indonesia. Menggunakan pendekatan kualitatif dengan metode studi kasus, penelitian ini mengeksplorasi bagaimana media sosial dimanfaatkan sebagai alat komunikasi budaya di era digital yang serba cepat. Data diperoleh melalui wawancara mendalam dengan pengelola akun, akademisi budaya, Social Media Specialist, serta pengikut akun @Chinese_Server. Selain itu, observasi terhadap konten akun dilakukan untuk menganalisis jenis unggahan, seperti sejarah, tradisi, kuliner, dan perayaan budaya Tionghoa, serta keterlibatan audiens melalui fitur interaktif. Hasil penelitian menunjukkan bahwa Instagram sebagai platform berbasis visual sangat efektif dalam menyampaikan informasi budaya melalui konten yang kreatif, menarik, dan edukatif. Akun ini berhasil membangun kesadaran, keterlibatan, serta kebanggaan budaya di kalangan generasi muda Tionghoa Indonesia. Penelitian ini memberikan wawasan baru tentang pemanfaatan media sosial sebagai sarana pelestarian budaya, strategi komunikasi digital, serta perannya dalam memperkenalkan identitas budaya di tengah derasnya arus globalisasi dan modernisasi.